The role of physical environment in leisure service consumption: evidence from a ski resort setting - Chua, Bee Lia; Lee, Sanghyeop; Huffman, Lynn; Hyun, Suk Choi (Taylor & Francis, 2015)
Despite the importance of physical environment in hedonic service consumption, little is known about the extent to which physical environment influences ski resort visitors’ cognition, emotion, and behaviors. This study investigated the relationships among physical environmental stimuli (i.e., layout accessibility, aesthetics, cleanliness, and other visitors), perceived quality of physical environment, excitement, and behavioral intentions in ski resort. This study also attempted to test the moderating role of enduring involvement in the formation of behavioral intentions. Results showed that cleanliness and other visitors significantly and positively influenced visitors’ perceived quality of physical environment and excitement. The results suggest that physical environment is of great importance for the ski resort business. Perceived quality was indeed a significant predictor of excitement, which, in turn, positively influenced behavioral intentions. Finally, the study found that the effect of excitement on behavioral intentions was significant across high and low enduring involvement groups.